0

# Solve the Trigonometry Identity

cosx = (1- tan^2 x/2)  /  1 + tan^2 x/2)

Completely stuck.

### 2 Answers by Expert Tutors

Michael F. | Mathematics TutorMathematics Tutor
4.7 4.7 (7 lesson ratings) (7)
0
cosx = (1- tan^2 x/2) / 1 + tan^2 x/2)
cosx= (1- tan^2 x/2) / sec^2 x/2=(1- tan^2 x/2)cos^2 x/2=cos^2 x/2-sin^2 x/2=cos x

Kirill Z. | Physics, math tutor with great knowledge and teaching skillsPhysics, math tutor with great knowledge...
4.9 4.9 (174 lesson ratings) (174)
0
tan(x/2)=sin(x/2)/cos(x/2), by definition.

1-tan2(x/2)=1-sin2(x/2)/cos2(x/2)=[cos2(x/2)-sin2(x/2)]/cos2(x/2);

Now remember that cos(a+b)=cos(a)cos(b)-sin(a)sin(b) If a=b=x then cos(2x)=cos2(x)-sin2(x). Apply this to the expression above to get:
1-tan2(x/2)=cos(x)/cos2(x/2);

Now similarly we can get:

1+tan2(x/2)=1+sin2(x/2)/cos2(x/2)=[cos2(x/2)+sin2(x/2)]/cos2(x/2);

Now recall basic trigonometric identity: cos2(x)+sin2(x)=1; Thus we obtain:

1+tan2(x/2)=1/cos2(x/2);

Finally, [1-tan2(x/2)]/[1+tan2(x/2)]=[cos(x)/cos2(x/2)]/[1/cos2(x/2)]=cos(x), since cos2(x/2) factors cancel out.